Relocation Study of Flores Sea Hypocenter (Mw = 7.3) Based on Single Station Estimation Using ObsPy - Khusnani, Azmi; Anggraini, Ade; Jufriansah, Adi; Zulfakriza, Zulfakriza; Pramudya, Yudhiakto; Margiono; Wae, Konsenius Wiran (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
One area in Indonesia that is prone to disasters is the Flores Sea area, which has the potential for earthquakes to trigger tsunamis. This is due to the location of Flores, which is in a subduction zone that originates from the collision of the Indo-Australian (South) and Eurasian plates. Inaccuracies in earthquake locations are influenced by differences in residual travel time values, mathematical solutions to location problems, and inaccuracies in the seismic velocity model used. The accuracy of determining the hypocenter of an earthquake influences the location of the earthquake source, which will later be used as a reference in appropriate earthquake disaster mitigation planning. Based on this, an analysis of earthquake hypocenter data is needed, so it is important to carry out research. This research aims to relocate the hypocenter using ObsPy with a single station. The results obtained show that the Python package, namely ObsPy, can carry out data retrieval commands through filtering, detrending, normalisation, and determining data request parameters, such as the start and end times of the desired data, location, network, and data type. This research contributes to the field of seismology because the process of determining the hypocenter requires a relatively short time. Apart from that, the accuracy obtained also provides accurate values.